Identifying molecular targets from herbicide resistance pathways for crop improvement - Kramer, William B., author; Gaines, Todd A., advisor; Dayan, Franck E., committee member; Pozniak, Curtis, committee member; Mason, Esten, committee member (Colorado State University. Libraries, 2026)
Herbicide resistance in weeds represents one of the greatest threats to yield stability in agricultural systems. Identifying the molecular mechanisms underlying herbicide resistance pathways provides important insight into herbicide mode of action and offers opportunities to leverage this knowledge for crop improvement. The research presented integrates physiological, transcriptomic, biochemical, and heterologous validation approaches to identify and functionally validate genes associated with herbicide resistance with the goal of identifying gene targets that can be used to enhance crop performance. First, variation in crop safety to the ACCase inhibitor quizalofop-P-ethyl (QPE) was investigated in CoAXium wheat, where Crescent AX consistently shows higher tolerance than AP18 AX despite both lines carrying ACCase target site resistance. Using cloquintocet-mexyl (CM) as a tool to induce genes associated with herbicide metabolism, Crescent exhibited reduced accumulation of quizalofop acid relative to AP18, stronger activation of safener responsive transcription, elevated glutathione S-transferase (GST) activity, and higher endogenous glutathione pools. RNA sequencing revealed broader and stronger induction of detoxification genes in Crescent, including enrichment of tau and phi class GSTs. Two candidates, TaGSTF1 and TaGSTU1, were prioritized based on homology to Group 1 herbicide metabolizing GSTs in grass weeds and were functionally validated. Recombinant enzyme assays confirmed both proteins conjugate quizalofop acid to form a glutathione conjugate, and Crescent displayed consistently higher expression and catalytic activity. A 115 bp deletion in the TaGSTU1 promoter unique to Crescent provides a plausible cis regulatory basis for elevated transcription. Collectively, these results link improved CoAXium crop safety to integrated metabolic advantages and identify TaGSTF1 and TaGSTU1 as actionable candidates and marker targets for breeding. Second, the molecular basis of non target site resistance to the ALS inhibitor imazamox (IM) was resolved in a feral rye population lacking ALS target site mutations. RNA sequencing of segregating resistant and susceptible F2 plants identified two cytochrome P450 candidates, CYP81A52 and CYP72A1365, based on constitutive and inducible expression patterns and homology to previously validated metabolic resistance genes. Functional validation in Arabidopsis confirmed that both candidate CYPs reduced IM accumulation and increased the O-demethylated metabolite, supporting a conserved detoxification pathway. Additional yeast expression assays further supported CYP mediated IM depletion further verifying the role of CYP activity in IM metabolism. These findings establish both CYP81A52 and CYP72A1365 as major drivers of IM metabolism in feral rye. Third, resistance to the synthetic auxin herbicide dicamba was translated across species by transferring a mutant AUX/IAA16 allele from kochia into tobacco. Comparative sequence and phylogenetic analyses supported conservation of key AUX/IAA and TIR1/AFB components required for receptor interaction. Transgenic tobacco expressing the kochia AUX/IAA16 mutant allele exhibited significantly increased dicamba tolerance without obvious vegetative growth penalties, demonstrating that disruption of auxin signaling at the degron-based co-receptor interface is sufficient to confer resistance in a heterologous crop background. Together, this research demonstrates that herbicide resistance pathways in weeds and tolerant crops uncover transferable molecular targets for crop improvement. By identifying GST mediated conjugation, CYP mediated metabolism, and auxin signaling components as actionable targets, this work delivers validated candidates, mechanistic insight, and practical molecular resources to support the development of enhanced herbicide metabolism and more resilient cropping systems.